ANALISIS KESTABILAN JALAN GIRIAN - KEMA PADA DAERAH PERBUKITAN MINAHASA UTARA - Pricilia Imanuela Jozias; Gregorius Sandjaja Sentosa (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2021)
The construction of a highway in a hilly area requires attention to the stability of the land on which the road body is laid. On the widening of the road between the cities of Girian-Kema, North Sulawesi, the road body is designed to pass through hillside areas that have a slope of about 36°. In designing the road body in the hilly area must be considered the stability of the slopes on the left and right side of the road, the ability to support the soil and other structures so that the road is in a safe condition. To check the safety of this roadway, three locations of the most critically considered points will be selected to fail. At the location, slope stability analysis was carried out using the MIDAS GTS NX program and obtained the most critical security factors ranging between 1,1 and 1,4. To find out the carrying capacity of the soil, calculated the possibility of roads supporting the most extreme load using standard a crated load of 80 kN, from the analysis is known that the stress that occurs if strengthened with soil geogrid can support the load better by 46,1042 kN/m2, and obtained efficiency of 18,83%.Pembuatan jalan raya di daerah perbukitan memerlukan perhatian terhadap kestabilan tanah tempat badan jalan diletakkan. Pada pelebaran jalan antar kota Girian-Kema, Sulawesi Utara, badan jalan dirancang harus melewati daerah lereng perbukitan yang memiliki kemiringan lereng sekitar 36°. Dalam merancang badan jalan pada daerah perbukitan tersebut harus diperhatikan kestabilan lereng yang berada di kiri dan kanan jalan, kemampuan daya dukung tanah dan struktur lainnya agar jalan berada dalam kondisi aman. Untuk memeriksa keamanan lintasan jalan ini, dipilih tiga lokasi titik yang dianggap paling kritis akan mengalami kegagalan. Pada lokasi tersebut dilakukan analisis kestabilan lereng dengan menggunakan Program aplikasi MIDAS GTS NX dan diperoleh Faktor kemanan paling kritis berkisar antara 1,1 dan 1,4. Untuk mengetahui daya dukung tanah, dihitung kemungkinan jalan mendukung beban yang paling ekstrem menggunakan beban gandar standar 80 kN, dari analisis diketahui bahwa tegangan yang terjadi jika diperkuat dengan geogrid tanah dapat mendukung beban dengan lebih baik sebesar 46,1042 kN/m2, dan diperoleh efisiensi 18,83%.